2018
DOI: 10.1080/09638288.2018.1462412
|View full text |Cite
|
Sign up to set email alerts
|

Music therapy applied to complex blast injury in interdisciplinary care: a case report

Abstract: Music therapy has optimized the rehabilitation of a service member through assisting the recovery process on a continuum from clinic to community. Implications for Rehabilitation Music therapy in stand-alone sessions and in co-treatment with traditional disciplines can enhance treatment outcomes in functional domains of motor, speech, cognition, social integration, and quality of life for military populations. Music therapists can help ease discomfort and difficulty associated with rehabilitation activities, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Music techniques are used to address motor function, social skills, emotional regulation, coordination, self-expression and personal growth across the lifespan, from neonates to seniors. Music therapy has been offered in the VHA for decades and recently has been integrated into interdisciplinary care models within the DoD [26]. Traditionally, evidence-based music therapy has been positioned in military healthcare as a clinical treatment that is conducted on-site (i.e., military installation or treatment facility) by a MT-BC [27].…”
Section: Evolving Integration Of Music Therapy Telehealth and Militmentioning
confidence: 99%
“…Music techniques are used to address motor function, social skills, emotional regulation, coordination, self-expression and personal growth across the lifespan, from neonates to seniors. Music therapy has been offered in the VHA for decades and recently has been integrated into interdisciplinary care models within the DoD [26]. Traditionally, evidence-based music therapy has been positioned in military healthcare as a clinical treatment that is conducted on-site (i.e., military installation or treatment facility) by a MT-BC [27].…”
Section: Evolving Integration Of Music Therapy Telehealth and Militmentioning
confidence: 99%
“…His score was 65, indicating moderate anxiety. International studies have shown that music therapy can improve the mood of patients, promote mental health, and reduce anxiety and depression symptoms[ 33 - 35 ]. Chu et al [ 36 ] and others have shown that music therapy can improve anxiety and depression in patients with Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with quadriplegia, singing can improve projected speech intensity and phonation length, as well as mood, with results maintained at six-month follow-up (766). For patients with blast injuries, music therapy supported breathing, strength endurance, range of motion, task attention, articulation, social integration, quality of life and motivation (767). Listening to music reduced agitation in patients with cognitive impairment following traumatic brain injury (768), while art therapy supported coping and acceptance (769).…”
Section: Other Acquired Brain Injuriesmentioning
confidence: 99%